Issues Challenging Food Security Goals in the Era of Disruptive Change and Opportunities to Revisit Extension Education Strategies - Wayne G. Ganpat; Marcus N. A. Ramdwar (Journal of International Agricultural and Extension Education, 2021)
This study examined the challenges to the achievement of food security goals and the role of Extension Advisory Services (EAS) at a time when the world is faced with the double burden of an immediate pandemic in themidst of ongoing climate change events. EAS have always played vital roles in past emergencies around the world and are being challenged to respond timely and appropriately in these times. The purpose of this paper was to (i) describe the impacts of disruptive changes on food systems across the world, (ii) present key agricultural education and extension responses to such changes and (iii) make recommendations to strengthen EAS responses. There was a focus on Covid-19 and climate change as disruptive changes. An internet-mediated approach to source information and a review of published literature were used to gather information. Results detailed the several impacts of Covid-19 and climate change in seven regions of the world, the impacts of both disruptive events on the four pillars of food security, and some global responses in the areas of agricultural education and extension to meet present challenges. Recommendations included the strengthening and deepening of collaboration of all extension service providers at country level to ensure coordinated responses, building stronger community resilience and extension research directed to assist the reengineering of extension organizations in terms of structure, leadership and management
Keywords: agriculture; extension; climate change; pandemic; food security